Prototipe Sistem Monitoring dan Kendali Suhu Box Kubikel 20 kV Berbasis Long Range (LoRa) - Muhamad Ariandi; Yoza Risti Oktaria (Universitas Budi Darma, 2023)
Electricity distribution often faces problems, one of which is interference with the 20 kV cubicle box caused by corona due to changes in temperature and condensation. This disturbance can cause arcing between the insulator and live parts. One solution is to use a heater and exhaust fan to maintain temperature and humidity. This study proposes a prototype to combine temperature and control heaters and exhaust fans automatically. Integrated sensors help monitor the temperature in the cubicle. Using a temperature sensor (DHT 22) shows high accuracy, and a current sensor (SCT 013) is suitable for exhaust fans and heaters. When the sensor is ready, the DHT 22 sensor will read the temperature in the room. If the reading temperature exceeds 40°C, then the exhaust fan will turn on to remove hot air in the cubicle box, whereas if the temperature is below 40°C the heater will turn on. If the detected temperature exceeds 43°C, and the exhaust fan does not turn on, a notification will appear on Blynk to immediately check the exhaust fan for errors. Meanwhile, if the temperature detects the cubicle box below the temperature of 37°C, a heater error notification will appear. The SCT 013 current sensor will detect the amount of current flowing in the exhaust fan and heater with the help of Esp32 as a microcontroller. This prototype utilizes LoRa technology for remote communication and sends notifications via the Blynk application. Tests show that this tool can help operators effectively monitor and control cubicle box temperature.